Badi'uzzaman Said Nursi on Philosophy of Education and Its Implications for the Muadalah Pesantren Model in Indonesia - Ahmad Siddiq (University of Darussalam Gontor, Indonesia, 2021)
Islamic education today is undergoing many shifts. Starting from the emergence of dualism in the education system and the confusion of islamic education goals that exist in modern educational institutions today. This is due to the confusion of the foundation of educational philosophy as a result of the westernization and secularization carried out by Western educational models that have developed in many Islamic countries. Badiuzzaman Said Nursi is a figure who strongly opposes the education of this Western model, Nursi argued that education should be based on faith and tawhid, religious science and modern science should be taught side by side and not separately. This paper aims to analyze Badiuzzaman Said Nursi's thinking in reforming Islamic Education based on his ideas about Madrasah al-Zahra in Turkey and its relevance to the model of education in Indonesia. This research is qualitative research and literature type using descriptive methods and analysis. The data used is the work of Badiuzzaman Said Nursi Risale-i Nur, and data obtained from papers, journals, and writings related to research topics. The study found that the idea of establishing Madrasah al-Zahra by Badiuzzaman Said Nursi was a comprehensive model of Islamic education. This model can be a solution to the problem of Dualism of Islamic education in the world in general and in Indonesia in particular, and its relevance to be applied to Pesantren Muadalah in Indonesia.